Ghosts of archive - Harris, V. S., author.
1 online resource (x, 155 pages).
Keywords: "'Ghosts of Archive' draws on the discourses of deconstruction, intersectionality and archetypal psychology to mount an argument that archive is fundamentally and structurally spectral and that the work of archive is justice. Drawing on more than twenty years of the author's research on deconstruction and archive, the book posits archive as an essential resource for social justice activism and as a source, or location, of soul for individuals and communities. Through explorations of what Jacques Derrida termed 'hauntology', Harris invites a listening to the call for justice in conceptual spaces that are non-disciplinary. He argues that archive is both constructed in relation to and beset by ghosts--ghosts of the living, of the dead and of those not yet born--and that attention should be paid to them. Establishing a unique nexus between a deconstructive intersectionality and traditions of 'memory for justice' in struggles against oppression from South Africa and elsewhere, the book makes a case for a deconstructive praxis in today's archive. Offering new ideas about spectrality, banditry, and archival activism, 'Ghosts of Archive' should appeal to those working in the disciplines of archival science, information studies and psychology. It should also be essential reading for those with an interest in social justice issues, transitional justice, history, philosophy, memory studies and postcolonial studies"--